From goals to joules: A quantitative approach of interlinkages between energy and the Sustainable Development Goals. (April 2019) - Santika, Wayan G.; Anisuzzaman, M.; Bahri, Parisa A.; Shafiullah, G.M.; Rupf, Gloria V.; Urmee, Tania
Abstract: Energy is a key enabler in achieving the Sustainable Development Goals (SDGs) as energy plays the pivotal role in ending poverty and hunger, providing healthcare, education, and water, as well as sustaining economic growth and protecting the environment. Consequently, since the SDGs are executable only at local and national levels, mainstreaming the SDGs into local/national development planning will put pressure on the country's energy sector. Considering the broad scope of the SDGs, countries will prioritize different SDG targets based on their urgencies, resources, and capabilities. However, energy linkages with the SDGs and their targets are complex, with direct and indirect connections, synergies, and trade-offs. More importantly, there is a lack of capacity among policymakers to be able to develop an SDGs-responsive energy plan, as there is no guidance on how the impact of linkages can be translated into local/national energy planning. This study aims to examine the complexity of the interconnections between energy and the SDGs, as well as give examples of how these linkages can be quantified. Twenty-five SDG targets with direct links to energy are identified in this study, and a map of the multidimensional interaction between them are presented. The study also provides examples of quantification of the targets/indicators into their energy requirements. The results of the study will help energy planners and policymakers forecast energy demand more accurately for energy planning and policies under the SDGs regime.